Tertiary cystic white matter injury as a potential phenomenon after hypoxia-ischaemia in preterm f sheep. Issue 2 (9th March 2021) - Lear, Benjamin A; Lear, Christopher A; Davidson, Joanne O; Sae-Jiw, Jialin; Lloyd, Johanna M; Gunn, Alistair J; Bennet, Laura
Abstract: White matter injury, including both diffuse and cystic elements, remains highly associated with neurodevelopmental disability and cerebral palsy in preterm infants, yet its pathogenesis and evolution are still poorly understood and there is no established treatment. We examined the long-term evolution of white matter injury in chronically instrumented preterm fetal sheep (0.7 gestation) after 25 min of complete umbilical cord occlusion or sham occlusion. Fetal brains were processed for histology after 3 days ( n  = 9, sham n  = 9), 7 days ( n  = 8, sham n  = 8), 14 days ( n  = 9, sham n  = 8) and 21 days ( n  = 9, sham n  = 9) of recovery. At 3 and 7 days recovery, umbilical cord occlusion was associated with diffuse white matter injury, with loss of total and mature oligodendrocytes and reduced myelination in both the parietal and temporal lobes. At 14 days after umbilical cord occlusion, extensive microglial and astrocytic activation were observed in the temporal lobe. At 21 days recovery a spectrum of severe white matter degeneration was observed, including white matter atrophy, ventriculomegaly and overt cystic white matter lesions. The most severe injury was observed in the temporal lobe after 21 days recovery, including the majority of cystic lesions, persistent oligodendrocyte maturational arrest and impaired myelination. The spatial distribution of delayed white matter degeneration at 21 days recovery was closely related to the location of dense microglial aggregates at earlier time-points, implicating a role for exuberant inflammation originating from microglial aggregates in the pathogenesis of cystic white matter injury. The delayed appearance of cystic injury is consistent with continuing tertiary evolution of necrotic cell death. This slow evolution raises the tantalizing possibility that there may a relatively long therapeutic window to mitigate the development of cystic white matter injury. Delayed anti-inflammatory treatments may therefore represent a promising strategy to reduce neurodevelopmental disability in the preterm infants. Abstract : Cystic white matter injury is the key pathological substrate of cerebral palsy in preterm infants. Lear et al. show that in fetal sheep cystic injury after severe hypoxia evolved over many weeks, raising the tantalizing possibility that substantial white matter protection may be possible with very delayed interventions. Graphical Abstract: